Implementasi Pancasila dalam Sistem Hukum Indonesia Era Modern - Agung, Bella Safitri (Philosophiamundi, 2025)
This study aims to analyze the implementation of Pancasila values within Indonesia’s legal system in the modern era, particularly in the formulation, application, and enforcement of law amid increasing globalization and technological development. This research employs a qualitative method using a literature study approach, drawing from books, scholarly articles, statutory regulations, and previous research relevant to the topic. The findings indicate that Pancasila remains a fundamental value source for Indonesia’s legal and political framework; however, its implementation faces challenges such as competing political interests, global cultural influences, and inconsistencies within the regulatory system. In the modern era, Pancasila principles such as social justice, humanity, and deliberation require actualization through legal reforms, strengthened legal ethics, and harmonization of regulations consistent with national identity. The study concludes that the implementation of Pancasila within Indonesia’s legal system is not only normative but must be realized in practice through adaptive and responsive legal policies grounded in the philosophical foundation of the nation.